Basal cell carcinoma: multimodal treatment and the role of neoadjuvant vismodegib - Pedro Carvalho Martins; Rita Valença Filipe; Rui Barbosa; Ivo Julião; Rosa Azevedo; Matilde Ribeiro; Abreu de Sousa (University of São Paulo, 2019)
Basal cell carcinoma (BCC) is the most common skin cancer. It generally has an indolent course with low rates of metastasis and mortality. However, BCC is locally invasive and can cause significant morbidity due to destructive local spread. We report our experience with a patient who was referred to our skin cancer unit due to a previously neglected lesion on the parietal region of the scalp, which had developed for 7 years. The patient was prescribed vismodegib on the basis that surgery could cause excessive functional and aesthetic damage. The patient had an objective partial response after 20 months of treatment. He was then submitted to radical skin excision, leaving a large defect that was reconstructed using a free latissimus dorsi muscle flap. The patient recovered well, and at the 1-year follow-up there were no signs of local recurrence. Our case demonstrates the value of vismodegib treatment prior to surgery in a locally advanced, high-risk scalp BCC and highlights the importance of an individualized and specialized approach with these patients, within a multidisciplinary team